1999
DOI: 10.1002/(sici)1096-9918(199908)28:1<3::aid-sia609>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Surface analysis and bioreactions of Ti- and V-containing a-C : H

Abstract: Amorphous hydrogenated carbon films (a‐C : H) containing different amounts of Ti or V were produced by combined plasma‐activated chemical vapour deposition and d.c. magnetron sputtering. New bioactive materials resulted from the combination of the excellent tribological and biological properties of the a‐C : H matrix with the biological response to the incorporated metals. By adding Ti to the a‐C : H matrix, an enhanced differentiation of osteoblast‐ and reduced osteoclast‐like cell activity was achieved, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 10 publications
0
14
0
1
Order By: Relevance
“…Osteoclast is habited by the addition of Ti into the DLC and then bone marrow cells differentiate into bone resorbing cells. It is believed that Ti-DLC film is not only used as a coating and passive film, but also improved fixation and enhanced oseto/osseointegration [28,30]. As stated above, titanium doping into DLC film can improves biocompatibility obviously.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…Osteoclast is habited by the addition of Ti into the DLC and then bone marrow cells differentiate into bone resorbing cells. It is believed that Ti-DLC film is not only used as a coating and passive film, but also improved fixation and enhanced oseto/osseointegration [28,30]. As stated above, titanium doping into DLC film can improves biocompatibility obviously.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, DLC film is a spurious base coating to be alloyed with various elements. The properties of DLC film can be promoted to include certain amounts of additional elements, such as F, N, O, Cu, V, Ti, Ta and their combinations [25][26][27][28], into the films and still maintain the microstructure without any phase transformation. Among them, titanium is a biocompatible material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…B. CF 4 , CH 4 , N 2 , V, Ag, Ti) mit unterschiedlichen Partialdrü-cken beeinflusst. Schichten mit auf den jeweiligen Einsatzzweck zugeschnittenen Volumen-und Oberflächeneigenschaften (Elastizität, Oberflächenspannung, innere Spannung, Härte, Reibung, biologisches Verhalten [15,16]) können durch einen geeigneten Prozessablauf auf praktisch jedes beliebige Material aufgebracht werden. Ausschlaggebend für den diamantähn-lichen Charakter der a-C:H-Schichten ist der Anteil an sp 3 -Bindungen im metastabilen amorphen Netzwerk aus sp 2 -und sp 3 -gebundenen Kohlenstoffatomen (Diamant =100% sp 3 , Graphit =100% sp 2 ).…”
Section: Studiendesign Und Untersuchungsmethodenunclassified
“…Diamondlike carbon-calcium oxide composite films have been also been created that promote bone formation and growth. [90] Morphology and proliferation studies involving L929 mouse fibroblasts have shown that these films contribute to healthy cell morphology and increased cell proliferation. It is believed that calcium carbonate, which exhibits bioactive properties, is incorporated within these films.…”
Section: Pulsed Laser Deposition Of Diamondlike Carbon-metal Compositmentioning
confidence: 99%